Effects of gamma radiation on chemical and antioxidant properties, anti-hepatocellular carcinoma activity and hepatotoxicity of borututu - Pereira, Carla (2014)
Borututu is a well-known medicinal plant in Angola for the treatment of liver diseases and for the prophylaxis of malaria. Our research group reported, in a recent study, that its infusion, pills and syrups display significant antioxidant and anti-hepatocellular carcinoma activities. However, during the processing and storage, it can be easily exposed to contamination that can lead to a microbial deterioration or insect infestation compromising its quality, shelf life, and efficiency. Herein, we investigated the effect of gamma irradiation, one of the most promising decontamination methods for many foodstuffs and plant materials, at different doses (1 and 10 kGy) on borututu regarding its nutritional value, lipophilic (fatty acids and tocopherols) and hydrophilic (free sugars and organic acids) compounds, antioxidant and anti-hepatocellular carcinoma activities. In general, the irradiation treatment did not appreciably affect the nutritional value of the studied plant, but the highest energetic contribution (383.83 kcal/100 g), total sugars (8.63 g/100 g), organic acids (3.31 g/100 g dw), total tocopherols (336.72 mg/100 g dw), and PUFA (32.75%) contents were found in the sample irradiated at 10 kGy. Furthermore, this sample presented also the highest levels of total phenolics and flavonoids and, in general, the highest antioxidant activity (EC50 values of 0.04 to 0.24 mg/mL for the methanolic extract and 0.03 to 1.34 mg/mL for the infusion). Irradiated samples kept the anti-hepatocellular carcinoma activity, but a decrease was observed in the methanolic extract prepared from sample irradiated at 10 kGy (GI50 = 188.97 μg/mL). Overall, gamma irradiation proved to be a suitable technique of preservation of dried herbs without affecting the bioactive compounds.